Raman spectroscopic study of the conformational changes of thyroxine induced by interactions with phospholipid - Álvarez, Rosa M. S. (2002)
Comparison of the Raman spectra of thyroxine ( L-3,3',5,5'-tetraiodothyronine) in the pure state and in a 1:5 mixture with phosphatidylcholine reveals spectral differences that reflect structural changes of thyroxine induced by interactions with the phospholipid. These structural changes could be localized in specific parts of the thyroxine molecule on the basis of a vibrational analysis that was carried out by density functional calculations with the B3LYP hybrid functional applying the SDD effective core potential basis set. The calculated (and subsequently scaled) frequencies reveal a good agreement with the experimental data, which together with calculated IR and Raman intensities allow a plausible assignment of most of the IR and Raman bands. Thus, it is found that modes localized in the aromatic beta-ring and in the ether group as well as the C-I stretching modes of ring alpha are affected upon lipid interactions, indicating that thyroxine interacts with the phosphatidylcholine bilayer via penetration of the hydrophobic part of the molecule.